Fotossensibilização hepatógena em búfalos (Bubalus bubalis) em pastagens de Brachiaria decumbens no estado de Minas Gerais - Cairo Henrique Sousa de Oliveira (2011)
The objective of this research was report the hepatogenous photosensitization in buffalos during two outbreaks caused by the ingestion of Brachiaria decumbens in the Fortuna de Minas town, Brazil. Two young buffalos were checked in the outbreak 01 with photosensitization along with another eight animals without clinical signs belonging to the same sick group. In the outbreak 02 seven animals were checked with skin injuries and another nine, clinically healthy, raised under the same conditions in a neighbor county. All the animals were submitted through clinical exam and in order to determine the serum levels of gamma-glutamyl transpeptidase (GGT), aspartate transaminase (AST), direct bilirubin (BD), indirect bilirubin (BI), and total bilirubin (BT) which all are indicators of liver functions as well as urea and creatinina, which are indicators of kidney functions, serum was collected. Was performed histopathology of liver fragments from five animals. During the outbreaks and in every two months along the year, samples from the paddocks grass were collected where the animals got sick in order to evaluate the quantity of protodioscin saponin, along with observations of the pasture characteristics and daily data of rainfall. The clinical signs observed were apathy, weight loss, unquiet, scar retraction of the ears and intensive rash, intensive itch on the skin injuries, mainly, in the croup area, tail, neck and back limbs. The sings were very similar to the ones observed in other ruminants, but without the marking presence of icterus. Only the GGT enzyme presented levels statistically different (P<0.01) between intoxicated (n=17) and healthy animals (n=9) and this enzyme can be indicated for the liver injury evaluation in buffalos grazing B. decumbens. On microscopy the liver was observed foamy macrophages and hepatopathy injuries associated with the presence of crystals in bile ducts, found both in sheep and cattle intoxicated by grass from the gender Brachiaria spp. During the outbreaks the levels of protodioscin were above 3% and right after they were reduced to inferior levels below 0.80%, assuring the etiology of the liver injury. The outbreaks occurred in the beginning of the rainy season and there was positive correlation between saponin versus the quantity of rainfall as well as the quantity of green leaves in the pasture, concluding that the grass was more toxic in this period.